Transformation of Blockchain-Based Financial Recording Systems: Literature Review in Modern Accounting - Olivia, Monica; Ningrum, Wulan Wahyu; Gianni, Fitri (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study reviews the potential transformation of financial recording systems through the adoption of blockchain technology. Blockchain, as a decentralized digital ledger, enables transparent, secure, and immutable transaction recording. The study analyzes literature published from 2023 to 2025 and identifies key benefits, such as real-time reporting, automated auditing, reduced risk of data manipulation, and enhanced financial transparency. However, it also highlights major challenges, including high implementation costs, regulatory uncertainty, limited technological literacy among accounting professionals, and the complexity of integrating with legacy systems. The study concludes that effective blockchain adoption in modern accounting requires the development of digital accounting standards, targeted training programs to improve technological literacy, and collaboration between regulators, academics, and industry stakeholders. Further research is recommended to develop an implementation framework that aligns with accounting principles and professional ethics.